(untitled) (Al-Farooq Journal of Sciences, 2026)
This study investigates the thermal performance of a gravity-driven concentrating solar water heating system, where the collector employing a multi-lens optical array. The proposed design incorporates forty convex lenses where these lenses are arranged to concentrate solar radiation onto an aluminum absorber plate. A copper tube attached to the absorber surface to transfer heat to a circulating water with in the system. The flow of circulating water is achieved without the use of mechanical pump, relying entirely on hydrostatic pressure generated by elevating the storage tank above the collector. Outdoor experiments were conducted to evaluate the behavior of solar irradiance, components temperature, thermal energy gain within storage tank, and overall efficiency of the system. The experimental result shows strong correlation between solar irradiance and thermal response of the collector system. During the periods of peaks solar intensity effective, the aluminum absorber plate and copper tube exhibited rapid temperature increases, which indicates effective solar energy absorption and conductive heat transfer. Furthermore, a consistent temperature difference between the collector inlet and outlet conforming the continuous thermal energy transfer to working fluid. Meanwhile the storage tanks demonstrate a delayed thermal response due to higher thermal inertia and heat storage capacity. The highest thermal efficiency periods close to solar noon and a similar performance pattern was recorded over operating days. Analyzing of thermal energy showed effective energy storage throughout daylight hours and expected heat losses were noticed during periods of zero irradiance. Overall, the experimental result demonstrates the practical and effectiveness of the proposed pump-free concentrating solar water heating system. The study offering a simple and energy-efficient approach for solar water heating applications, particularly in regions characterized by high solar irradiation levels.